Maternal high-fat diet and risk of cardiovascular disease in offspring: a review of mechanisms, controversies, and interventions - Heyu Meng; Jianjun Ruan; Qing Wang; Fanbo Meng (Experimental Biology and Medicine, 2026)
A high-fat diet (HFD) is a well-established risk factor for coronary artery disease (CAD). Accumulating evidence indicates that maternal nutritional status before and during pregnancy critically influences long-term cardiovascular outcomes in offspring. This review systematically synthesizes current mechanistic, epidemiological, and clinical evidence regarding the impact of HFD on CAD while also examining its effects on broader cardiovascular phenotypes that are integral to CAD pathogenesis, such as endothelial dysfunction, cardiac remodeling, and metabolic derangements. A particular focus is placed on the potential effects of maternal pre-pregnancy HFD exposure on offspring CAD risk in adulthood. Existing studies suggest that HFD induces coronary injury primarily through metabolic dysregulation, endothelial dysfunction, and epigenetic reprogramming. Notably, maternal exposure to HFD during the perinatal period may predispose offspring to coronary artery disease via these mechanisms. Conversely, appropriate maternal nutritional interventions during pregnancy have shown promise in mitigating these adverse effects, although their long-term efficacy and underlying molecular mechanisms remain to be fully elucidated. Future research should prioritize large-scale prospective cohort studies with extended follow-up to determine the optimal timing, mechanisms, and efficacy of dietary interventions. Such evidence would provide a scientific foundation for developing preventive and therapeutic strategies aimed at reducing cardiovascular disease risk from the earliest developmental stages.